Table S4, Content and stable isotopic composition of total organic carbon (TOC) and total nitrogen (TN) for ODP cores at sites 964 and 967 - Felix J Elling; Jordon D Hemingway; Jenan Kharbush; Kevin W Becker; Catherine Ann Polik; Ann Pearson (PANGAEA, 2021)
Bulk organic carbon (OC) and nitrogen content and stable isotope compositions for ODP cores at sites 964 and 967, including: event name, sapropel layer, core, depth (top), depth (bottom), OC content (mean), OC content (std. dev.), OC d13C (mean), OC d13C (std. dev.), nitrogen content (mean), nitrogen content (std. dev.), d15N (mean), d15N (std. dev.), and C/N ratio. All content and isotope data were generated using a Thermo Scientific Delta V isotope ratio mass spectrometer run in continuous flow mode. Samples were acidified by fumigation prior to OC content and d13C analysis; samples were run without acidification for N content and d15N analysis. This work was supported by the Gordon and Betty Moore Foundation.
In: Elling, FJ et al. (2021): Mediterranean sapropel bulk organic matter and biomarker concentrations and carbon isotope compositions [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937082